THE RELATIONSHIP BETWEEN PARENTING STYLE AND THE DEVELOPMENT OF PRE-SCHOOL CHILDREN - Kusmawati, Iffah Indri; Argaheni, Niken Bayu; Sukamto, Ika Sumiyarsi; Putri, Noviyati Rahardjo; Linh, Nguyen Dieu (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2023)
Background: Parenting styles for children are given from an early age, which is a way of educating children to form personalities that will be carried into adulthood. Parenting styles will affect children's development both in gross motor and fine motor skills, personal and social interactions, and language.Objective: The aim of the study was to determine the strength of the relationship between parenting style and the development of pre-school children at Posyandu Kaliboto Karanganyar.Method: The research method is quantitative and cross-sectional. At Kaliboto Posyandu, the under-five population was studied by taking samples using the Slovin formula and obtaining 85 respondents who met the criteria of being parents and having children under the age of five (aged 3-5 years). The instruments used were a questionnaire for parents and the Denver Development Screening Test (DDST) sheet to measure children. Data analysis using Spearman rankResult: The results showed that 57.6% of parents practiced democratic parenting, and 62.4% of children under the age of five showed normal child development. The results of bivariate analysis with Spearman Rank obtained a p value of 0.000 and a positive correlation coefficient value of 0.547.Conclusion: There is a relationship between parenting style and the development of medium-strength preschool-aged children at Posyandu Kaliboto. The parenting style applied by the majority is democratic, and the majority of preschool-aged children are normal. It is expected to be the basis for parents to apply parenting in a democratic manner in order to optimize the development of preschool children.